Impact of resistant starch: absorption of dietary minerals, glycemic index and oxidative stress in healthy rats - Nisa, Mahr Un (2024)
Background & aims: Resistant starch (RS) is a prebiotic fiber that has been scientifically shown to control the development of obesity. Prebiotic role of RS has also seen to be very important as it helps gut bacteria to regulate fermentation and fatty acid production. This study aimed to check the different levels of RS on glycemic index, oxidative stress and mineral absorption rate in healthy rat models. To evaluate these objectives, the trial was conducted for 40 days of follow up; 10 days were the adjustment period and the collection period over 30 days. Methods: Thirty-six healthy female Wistar rats were divided into 4 groups of (9 animals each) NC (Normal Control: without resistant starch), RS0.20 (resistant starch: 0.20 g/kg body weight), RS0.30 (resistant starch: 0.30 g/kg body weight), RS0.40 (resistant starch: 0.40 g/kg body weight). All the diets were isocaloric and isonitroginous. Results: The impact of different levels of RS on the dry-matter intake (DMI) presented statistically significant results (p ≤ 0.05): DMI was reduced in RS (0.02) fed rats as compared to NC rats in first 3 weeks; and after 4th and 5th weeks, there was a DMI reduction of 28% in RS (0.04) fed rats. Moreover, there was no significant increase in the nutrient intake in all RS diets. The dry-matter (DM) digestibility was statistically significantly (P ≤ 0·05), which increased in all rats fed with different level of RS. The weight loss showed statistically significant results: RS (0.04) exhibited 19 g reduction in weight as compared with NC rats. Significant increase was observed in total oxidant status (TOS), in all the RS fed rats when compared with NC rats. The levels of Mg, Ca, Fe and Zn were shown to be decrease in feces analysis, which proves their better absorbance in gut. Statistically significant increase was observed in antioxidant capacity, whereas significant decrease was observed in the total weight of the animals, showing the role of RS in controlling obesity. Conclusions: Overall, significant results were found in all dosage level of RS but long term administration of the higher dosage level (RS0.40) may need to be studied for enhanced results. RS can help improve insulin sensitivity in overweight adults.